STATE OF SALINITY OF SOILS OF THE HISTORICAL MONUMENT SARYKORGAN (Scientific journal of the Fergana State University, 2025)
Studying the reclamation condition of saline lands, analyzing the chemical elements in the soil, and studying the level of salinity are of great importance in increasing soil fertility. The salinity level of the soils of the historical monument hill of Sarykurgan was studied for the purpose of efficient use of land.